1998
DOI: 10.1055/s-1998-1705
|View full text |Cite
|
Sign up to set email alerts
|

A New Efficient Access to Glycono-1,4-lactones by Oxidation of Unprotected Itols by Catalytic Hydrogen Transfer with RhH(PPh3)4-Benzalacetone System

Abstract: Treatment of unprotected pentitols and hexitols with RhH(PPh 3 ) 4 -benzalacetone system leads exclusively to glycono-1,4-lactones in 60-96% yield.The literature records a number of methods for the conversion of diols to lactones in yields varying from good to poor. These include: silver carbonate on Celite, 1 stoichiometric RuCl 2 (PPh 3 ) 3 in benzene, 2 CuSO 4 -KMnO 4 , 3 tetrapropylammonium perruthenate-4-methylmorpholine Noxide, 4 and catalytic hydrogen transfer (C.H.T) [benzalacetophenoneRuH 2 (PPh 3 ) 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…NMR-scale reactions of -glucopyranose in [D 7 ]DMF have established that the initial oxidation products are in fact the δ-lactones, but control experiments with the readily accessible δ--gluconolactone (see above) showed that, under the same reaction conditions, the rhodium catalyst isomerizes them rapidly to the thermodynamically more stable γ-form (Scheme 2). [13,14] We have now discovered that Shvo's catalyst system, which is based on the dimeric ruthenium complex [(C 4 Ph 4 CO)(CO) 2 Ru] 2 (7), [15,16] also efficiently catalyzes the dehydrogenation of -gluco-, -manno-, and -galactopyranoses to the corresponding δ-lactones, but, with the exclusion of water, it does not effect the δ Ǟ γ isomerization of the kinetic to thermodynamic products.…”
Section: Introductionmentioning
confidence: 99%
“…NMR-scale reactions of -glucopyranose in [D 7 ]DMF have established that the initial oxidation products are in fact the δ-lactones, but control experiments with the readily accessible δ--gluconolactone (see above) showed that, under the same reaction conditions, the rhodium catalyst isomerizes them rapidly to the thermodynamically more stable γ-form (Scheme 2). [13,14] We have now discovered that Shvo's catalyst system, which is based on the dimeric ruthenium complex [(C 4 Ph 4 CO)(CO) 2 Ru] 2 (7), [15,16] also efficiently catalyzes the dehydrogenation of -gluco-, -manno-, and -galactopyranoses to the corresponding δ-lactones, but, with the exclusion of water, it does not effect the δ Ǟ γ isomerization of the kinetic to thermodynamic products.…”
Section: Introductionmentioning
confidence: 99%
“…[116] Am ilder alternative was demonstratedb yt he Uzan group in 1995 and 1998. [117] They reportedt he regioselectiveh ydrogentransfer oxidationo fu nprotected tetroses,p entoses, andh exoses in the presence of aR hH(Ph 3 ) 4 catalysta nd benzalacetone in DMF,y ielding the corresponding 1,5-lactones, followed by fast isomerization to the 1,4-glyconolactones, which were isolated in good to excellent yields.…”
Section: Aldonamidesmentioning
confidence: 99%
“…[5] In sugars, this process typically affects the secondary hydroxy functions and the precursor molecules are transformed into keto-sugars. [6] There is an increasing interest in the selective transformation of glycerol into useful building blocks for the synthesis of fine chemicals based on simple and selective oxidation processes. [7] The direct conversion of an alcohol into a carbonyl compound using a dehydrogenative oxidation reaction in the first step and the immediate, subsequent conversion into another product in a tandem reaction using a single catalyst is an attractive approach for the direct transformation of alcohols into valuable chemicals.…”
Section: Introductionmentioning
confidence: 99%